Die Einsamkeit des Prekariats und die Bedürfnisse des "Wir": Warum es notwendig ist, das Konzept der gemeinsamen Bedürfnisse in die Definition des Prekariats aufzunehmen - Roberto Luppi (Europa-Kolleg Hamburg, Institute for European Integration, 2023)
In recent decades our societies have experienced the steady growth of the precariat, even though the contours of this group still remain somewhat vague. The essay aims at contributing to the specification of the precariat's definition, making use of the category of common needs. Indeed, this concept is deemed capable of: 1) playing a defining and aggregating function for the realities that populate the precariat; and 2) helping it in the recognition of common demands and claims to counter forms of systemic injustice. The category of common needs directs attention to aspects of the precariat's condition that are not only related to objective and - so to speak - material factors, but can be traced back to a condition of loneliness, as much psychological as determined by social mechanisms. In the paper, therefore, the identification of a (yet to be broadened) list of common needs is deemed to be a useful tool in combating the state of loneliness of the precariat, as well as contributing to its greater self-awareness.
Keywords: 320; Precariat; Precarity; Common Needs; Liberalism